A systematic review evaluating the efficacy and factor consumption of long-acting recombinant factor VIII products for the prophylactic treatment of hemophilia A. (1st December 2020) - Graf, Lukas; Yan, Songkai; Shen, Ming-Ching; Balasa, Vinod
Abstract: Aims: Long-acting (LA) recombinant FVIII (rFVIII) products with extended dosing intervals have been developed for the treatment of hemophilia A; however, no direct head-to-head trial has been conducted to compare the efficacy of these products. Materials and methods: A systematic literature search was conducted to identify published Phase III clinical trials of prophylactic LA rFVIII treatment in previously treated patients aged ≥12 years, with moderate-to-severe hemophilia A (endogenous FVIII levels ≤2%). Studies that did not meet these criteria, or did not report the included outcomes, were excluded. Bleeding rates and consumption were extracted and summarized; only data for the dosing frequencies indicated in the US product labels (which are similar to those indicated in the European Medicines Agency labels) were included. Results: Five articles met the inclusion criteria; these studies only included patients with severe hemophilia A. Treatment length, reported outcomes and dose (range: 20–65 IU/kg) varied between studies. Median annualized bleeding rate (ABR) (IQR) reported in the relevant studies was 1.14 (0.00–4.30), rVIII-SingleChain 2 or 3 times weekly; 1.6 (0.0–4.7), rFVIIIFc 2 times weekly followed by every 3–5 days; 1.9 (0.0–5.8), BAX855 2 times weekly; 1.18 (0.00–4.25), N8-GP every 4 days; 1.9 (0.0–5.2) and 4.1 (2.0–10.6), BAY 94-9027 2 times weekly for the cohort who experienced >1 or <1 bleed in the study run-in phase, respectively. Median spontaneous ABR was 0.0 across studies reporting relevant data. Reported consumption was comparable among all LA products. Limitations: The primary limitation of this systematic review was the variation in study design and not all studies reported all desired outcomes, which limited the quantity of data available. Conclusions: This systematic review identified pivotal trial data for LA rFVIII products. Real-world evidence is needed to understand how these products perform in clinical practice.